Chronic gastroduodenitis associated with Helicobacter pylori in combination with giardiasis in children - T.V. Sorokman (Zdorovʹe Rebenka, 2022)
Background. The results of most scientific studies in recent years have made it possible to reconsider the traditional ideas about the pathogenesis of chronic gastroduodenitis (CGD) from a new perspective. The purpose was to investigate the clinical and endoscopic features of СGD associated with Helicobacter pylori (H.pylori) in combination with giardiasis. Materials and methods. The study included 105 children aged 7–16 years divided into two groups: I — patients with СGD associated with H.pylori (n = 29), II — children with СGD associated with H.pylori in combination with giardiasis (n = 76). The study was conducted on the basis of the gastroenterology department of the Chernivtsi Regional Clinical Hospital during 2020–2021 and included esophagogastroduodenofibroscopy, ultrasound examination of the abdominal cavity, rapid urease test, determination of specific M, A and G immunoglobulins to H.pylori CagA antigen in the blood serum and in feces, fecal examination for Giardia lamblia (G.lamblia) antigen by polymerase chain reaction. Results. The most severe infection of G.lamblia occurred in children aged 9–13 years (17 people out of 29 positive). The number of children with G.lamblia increased between the ages of 7–9 and 10–12 years (p < 0.05, χ2 = 5.236, z = 1.899) and decreased in the age of 13–16 years (p < 0.05, χ2 = 7.144, z = 2.567). Patients with giardiasis complained of irritability (p < 0.05), headache, dizziness, restless sleep, heart pain, and they were more likely to show signs of intoxication and skin syndromes. Children of group I were most often diagnosed with corpus gastritis (p < 0.05), antral gastritis (p < 0.05) or pangastritis (p < 0.05) with focal hyperplasia (p < 0.05), and children of group II — with mainly antral gastritis, as well as severe duodenitis (p < 0.05). A characteristic endoscopic feature in children of group II was follicular duodenitis. Inflammatory process in group II significantly more often (p < 0.05) was severe (81.5 %) and active (77.6 %) and was associated with eosinophilic infiltration (51.3 %), microerosions and foci of lymphoid tissue hyperplasia (6.5 %). Conclusions. The clinical course of СGD associated with H.pylori in combination with G.lamblia is characterized by more pronounced dyspeptic symptoms with signs of intoxication and skin syndromes. According to the results of endoscopic examination, patients suffered from СGD associated with H.pylori infection had esophagitis, corpus gastritis, antral gastritis and pangastritis (p < 0.05) significantly more often. Children with G.lamblia invasion had severe follicular duodenitis (p < 0.05).